The Numerical Competency of Two Bird Species (Corvus splendens and Acridotheres tristis) - Rahman, Nor Amira Abdul (Penerbit Universiti Sains Malaysia, 2014)
We conducted a series of experiments to test the numerical competency of two species of birds, Corvus splendens (House Crow) and Acridotheres tristis (Common Myna). Both species were allowed to choose from seven different groups of mealworms with varying proportions. We considered the birds to have made a correct choice when it selected the food group with the highest number of mealworms. Our overall results indicated that the Common Myna is able to count numbers (161 successful choices out of 247 trials) better than House Crows (133 successful choices out of 241 trials). We suspect that House Crows do not rely on a numerical sense when selecting food. Although House Crows mostly chose the cup with more mealworms (from seven food item proportions), only one proportion was chosen at rate above random chance. The Common Myna, however, were slow performers at the beginning but became increasingly more capable of numerical sense during the remainder of the experiment (four out of seven food proportion groups were chosen at a rate above random chance).